Physical development, the level of physical and technical preparedness of 14 - 15 year old young weightlifters of different weight categories groups - Lutovinov, Iu. A.; Martin, V. D.; Oleshko, V. G.; Lisenko, V. N.; Tkachenko, K. V. (Physical Education of Students, 2014)
Purpose : explore physical development, the level of physical and technical preparedness of young weightlifters of different weight categories groups. Material : the study involved 36 athletes. Athletes age 14-15 years. Results : present physical development, the level of physical and technical preparedness of athletes who are preparing for the championship of Ukraine. Found that indicators body length athletes tend to increase with increasing weight category groups - by 15,0% (p <0,05). It is estimated that the active body mass index increases with sportsmen groups weight categories - by 20,0% (p <0,05). It is proved that the difference between the strength of the left and right brushes all weight categories of groups - 2.4%. The analysis of the indicators in the control of technical readiness exercises in the snatch. Conclusions : to determine the trends of physical development, the level of physical and technical preparedness of athletes of different groups of weight categories. Indicator is dynamometry athletes increased with increasing weight category groups - by 47,7% (p <0,05).